Promoting the Responsibility to Protect through Non-State Armed Groups - Nnawulezi, Uche; Nwaechefu, Hilary (Indonesian Journal of Law and Society, 2022)
Promoting responsibility to protect through non-state armed groups will immensely reduce humanitarian crises around the globe. This paper aimed to analyze in detail the notion of responsibility to protect through non-state armed groups and its constitutive elements and set out a legal test that will expand the pre-existing notion of humanitarian intervention. In doing so, the paper advanced several conceptual arguments that focused on the responsibility to protect. The paper analyzed its views in light of contemporary developments on the responsibility to protect. The paper adopted a diagnostic approach based on a review of the literature and an evidence-based analysis of the humanitarian engagement of non-state armed groups. This paper showed the importance of reiterating that if the future of humanitarian intervention must be guaranteed, the need to take cognizance of the significant role of non-state armed groups in conflict mediation or intervention should not be overlooked. It is advanced that the continued neglect of non-state armed groups in conflict mediation or intervention portends a clog in responsibility to protect during armed conflicts. KEYWORDS: Responsibility to Protect, Non-State Actors, Armed Groups.